Effect of pH on the Microstructural Morphology and Phase Transformation of TiO2 Nanopowders Prepared by Sol-Gel Method - Sung Lim, Chang (Asian Journal of Chemistry, 2014)
Titanium dioxide nanoparticles were successfully prepared by a sol gel method. The resultant microstructural morphology and phase transformation on the variation pH were investigated. The influence of pH on the reaction morphology of using a titanium tetra-isopropoxide was evaluated depending on the amounts of the catalysts such as HCl and NH4OH. The microstructural morphology and phase transformation of TiO2 particles prepared by the hydrolysis of titanium tetra-isopropoxide were strongly influenced by the presence of the catalysts. The phase transformations of amorphous Ti(OH)4 to anatase TiO2 and the anatase to rutile were significantly influenced by the type and the amount of the catalysts.